"ÉTUDE DE L'EFFET DES CHANGEMENTS DE CONDITIONS OPERATIONNELLES SUR LES PERFORMANCES DES PANNEAUX PHOTOVOLTAÏQUES" - بلقيس, محلوس; لطيفة, زهري; يوسف, ترشة (University of El-Oued, 2022)
"This work is experimental study of the effect of operational on the performance of two technically similar photovoltaic panels. Exerimental work was carried on may 11, 2022 on the two PVs at the level of the Professional Training Center ""Echahid CHADOU Elhachemi"" in Reguiba, El oued Province, Algeria. The experimental work included many practical scenarios, and through it was concluded that to get the best performance. The till angle should be b2=45° And the solar panel system should be equipped with double solar tracking system, with the need the recieving area of the photovoltaic system clean, and this can be washed regulary. The results obtained are very important and very reasonable. One of the most important of this study is that the student of this desertation have acquired significant experience in the instalation, use and operation of photovoltaic panels, which is one of the axes of solar renewable energies that Algeria seeks to extend its uses in many industial fields, households, public and private institutions."هذا العمل عبارة عن دراسة تجريبية لتأثير الظروف التشغيلية والمناخية على آداء لوحين ضوئيين متشابهيين تقنيا. تم تنفيذ العمل التجريبي في 11 مايو 2022 على محطتين للطاقة الشمسية على مستوى مركز التدريب المهني " الشهيد شادو الهاشمي" بمنطقة الرقيبة ولاية الوادي الجزائر. اشتمل العمل التجريبي على العديد من السيناريوهات العملية، ومن خلالها استنتج أنه للحصول على أفضل أداء يجب ان تكون زاوية الميل b2=45 درجة وأن يكون نظام الالواح الشمسية مزودا بنظام مزدوج لتتبع الطاقة الشمسية مع الحاجة الى الحفاظ على منطقة الاستقبال للنظام الكهروضوئي نظيفة، ويمكن غسلها بانتظام. النتائج التي تم الحصول عليها مهمة جدا ومعقولة جدا. من أهم هذه الدراسة أن طلاب هذه الرسالة قد اكتسبو خبرة كبيرة في تركيب واستخدام وتشغيل الالواح الكهروضوئية، والتي تعد أحد محاور الطاقة الشمسية المتجددة التي تسعى الجزائر الى توسيع نطاق استخدامها في العديد من المجالات، المجالات الصناعية والمنازل والمؤسسات العامة والخاصة.
مذكرة ماستر تخصص كهروميكانيك
Keywords: Solar energie, Photovoltaic panels , Experemental study, Performance; الالواح الشمسية، الطاقة الشمسية، دراسة تجريبية، اداء